Socio-Economic Trade-offs of Large Hydropower Development for Community Livelihoods in Bagmati Province, Nepal - Neupane, Gunaraj; Pianrog, Yutthapong; Techato, Kua-anan; Ghimire, Hari Prasad (International Journal of Energy Economics and Policy, 2026)
Large hydropower development is widely promoted as a pathway for sustainable energy transition and economic growth, particularly in mountainous countries such as Nepal. However, its socio-economic implications at the community level remain contested. This study examines the impacts of large hydropower development on community livelihoods in Nepal’s Bagmati Province using secondary time-series data covering the period 2015–2024. Guided by the Sustainable Livelihoods Framework, the study employs descriptive analysis, correlation analysis, multiple regression, and factor analysis to assess relationships between infrastructure development, employment, income, environmental impacts, and displacement. The results reveal a clear development–displacement paradox. While infrastructure development and household income increased over time, environmental impacts emerged as the strongest driver of displacement, outweighing the mitigating effects of economic and infrastructure gains. Employment and income improvements alone were insufficient to offset livelihood disruption. Factor analysis identified two dominant pathways: an economic–infrastructure pathway that enhances physical and financial capital, and an environmental–displacement pathway that erodes natural capital and increases livelihood vulnerability. The findings highlight that environmental degradation plays a central role in shaping livelihood outcomes in hydropower-affected areas. The study contributes empirical evidence from a Himalayan context and underscores the need for hydropower policies that prioritize environmental safeguards, livelihood restoration, and inclusive development to achieve socially sustainable energy transitions.